Enhancement of dissolution of Telmisartan through use of solid dispersion technique surface solid dispersion - Bhumika Patel; R H Parikh; Deepali Swarnkar (Wolters Kluwer Medknow Publications, 2012)
The present study was aimed to increase the solubility of the poorly water soluble drug Telmisartan by using Surface solid dispersion (SSD) made of polymers like Poloxamer 407, PEG 6000 by Solvent evaporation method. The drug was solubilized by surfactants and/or polymers then adsorbed onto the surface of extremely fine carriers to increase its surface area and to form the SSD which give the more Surface area for absorption of the drug. A 2 2 full factorial design was used to investigate for each carrier the joint influence of formulation variables: Amount of carrier and adsorbent. Saturation solubility studies shows the improvement in solubility of drug batch SSD 8 give more solubility improvement than the other batch, in-vitro dissolution of pure drug, physical mixtures and SSDs were carried out in that SSDs were found to be effective in increasing the dissolution rate of Telmisartan in form of SSD when compared to pure drug. Also FT-IR spectroscopy, differential scanning calorimetry and X-ray diffractometry studies were carried out in order to characterize the drug and Surface solid dispersion. Furthermore, both DSC and X-ray diffraction showed a decrease in the melting enthalpy and reduced drug crystallinity consequently in SSDs. However, infrared spectroscopy revealed no drug interactions with the carriers.